Simulation of Physical, Chemical, and Biochemical Environmental Processes with Spreadsheets and VBA - Demir, Selami (BOND UNIV, FAC BUSINESS SCH INFORMATION TECHNOLOGY, 2021)
Dynamic simulation of physical, chemical, and biochemical reactions is usually difficult for environmental engineering students since most of water and wastewater treatment systems rely on several combinations of these reactions. Besides, the processes are so complex most of the time that numerical solution of differential equations by simple integration algorithms like Euler's method is not a viable option due to large margins of errors propagated. With more sophisticated algorithms like Runge-Kutta methods, on the other hand, the solution of related ordinary differential equations becomes a mathematical challenge for students. This paper presents a simple spreadsheet and programming solution to this mathematical challenge for teaching simulation of processes.
Keywords: Environmental processes; Modelling; Integration; Spreadsheets; Visual Basic for Applications; MS EXCEL TOOL; MATLAB; Education & Educational Research